Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/s22051957
|View full text |Cite
|
Sign up to set email alerts
|

Adapting a Dehazing System to Haze Conditions by Piece-Wisely Linearizing a Depth Estimator

Abstract: Haze is the most frequently encountered weather condition on the road, and it accounts for a considerable number of car crashes occurring every year. Accordingly, image dehazing has garnered strong interest in recent decades. However, although various algorithms have been developed, a robust dehazing method that can operate reliably in different haze conditions is still in great demand. Therefore, this paper presents a method to adapt a dehazing system to various haze conditions. Under this approach, the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…This implies that the haze distribution depends on scene depth, allowing the dehazing algorithm to handle various types of haze, from mild to dense. In a prior study [38], we introduced a framework for generating a piece-wise linear weight using the haziness degree estimator [37]. This weight is combined with the scene depth in a multiplicative manner to address different scenarios:…”
Section: Self-calibration On Haze Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies that the haze distribution depends on scene depth, allowing the dehazing algorithm to handle various types of haze, from mild to dense. In a prior study [38], we introduced a framework for generating a piece-wise linear weight using the haziness degree estimator [37]. This weight is combined with the scene depth in a multiplicative manner to address different scenarios:…”
Section: Self-calibration On Haze Conditionsmentioning
confidence: 99%
“…In [38], evaluation results indicated that dehazing performance for densely hazy images was unimpressive, suggesting that greater dehazing power might improve results. Consequently, in this study, we have modified the original weighting scheme by allowing the weight (ω) to extend beyond the range [0, 1], up to a predefined value of W, as illustrated in Figure 2b.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the proposed method, the enhanced equidistribution [31] supersedes SUD to improve the statistical reliability of the synthetic dataset. Additionally, the mini-batch gradient ascent with an adaptive learning rate [34] replaces SGA to reduce the convergence time.…”
Section: ) Scene Depth Estimationmentioning
confidence: 99%
“…To describe chrominance interpolation, we reused ch ij , cb ij , and cr ij to denote a component of Ch f , Cb t , and Cr t in the i-th row and j-th column, respectively. Given Ch f = {ch ij ∈ R}, Cb t and Cr t are obtained by interlacing Ch f with zeros, as (34) and (35) show.…”
Section: ) Color Gamut Expansionmentioning
confidence: 99%